Thermo-hydraulic effect of a convergent-divergent cold channel using MXene nanofluid for thermoelectric-based waste heat recovery system - Sahoo R.R.; Srivastava K. (My University, 2025)
Waste heat recovery seems technically and economically feasible to extract more power from the available system. Thermoelectric-based waste heat recovery is one such technique for direct heat-to-power conversion. Improvement in heat transfer is coherent with the efficiency of such systems. In the current study, the thermal and hydraulic performance of the cold side of the thermoelectric generator is investigated by replacing the conventional parallel channel with the channel having non-parallel walls for heat transfer gains with a 0.1% vol. fraction of MXene nanofluid coolant. Experiments are performed under uniform heat flux with convergent, divergent, and flat ducts for three non-parallel angles 00, 10, and 1.50 within the Reynolds number 700-2100. Moreover, all performance is compared subject to the constraints of the same mass flow rate, pressure drop, and pumping power. The result revealed that heat transfer efficiency rises with an increase in the converging and diverging angle. The divergent channel has a 15.62% and 17.18% greater value than convergent and smooth channels, respectively, at a Reynolds number of 2100. Also, compared to parallel channels, the pressure drop is greater in non-parallel channels. D-3 channel, and under identical pumping power and pressure drop conditions, D-2 performs better with a 0.1% vol. fraction MXene nanofluid coolant at identical mass flow rates. The flow acceleration or deceleration caused by the change in the cross-section of the channel has shown a strong influence on its heat transfer characteristic. The proposed design of the cold channel with MXene nanofluid will cause a profound enhancement in the power output of the thermoelectric system. © 2023, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.